Tensile Strength of Flexor Tendon Repair Using Barbed Suture Material in a Dynamic Ex Vivo Model - Zeplin, Philip H.; Henle, M.; Zahn, R. K.; Meffert, R. H.; Schmidt, K. (Journal of Hand and Microsurgery, 2012)
The purpose of this study was to compare two sutures; a knotted polydioxane with a knotless barbed in a 4-strand Kirchmayr-Kessler suture technique. Human flexor digitorum tendons were separated into four groups. Group 1 – polydioxane; Group 2 - barbed suture; Group 3 and 4 – same as group 1 and 2 with an additional peripheral running suture. In each group the repaired tendons were subjected to linear and cyclical loads. No difference in maximum tensile strength after linear and cyclical force could be detected between the knotted polydioxane suture and the knotless barbed suture. On linear force tests an additional circumferential repair increased the maximum tensile strength of both sutures. Cyclical force loading did not lead to a reduction of maximum strength. Following linear and cyclical loading the 4-strand barbed suture achieved maximum tensile strengths comparable to the 4-strand repair using the polydioxane suture. Barbed suture repair may offer the advantage of knotless suture techniques.
Keywords: Barbed suture; Load to failure; Tenorrhaphy; Dynamic testing; Tensile strength; Ex vivo